Mariculture wastewater treatment using electrochemically assisted submerged fixed bed bioreactor (E-SFBBR): Potential performance and pathways of nitrogen removal. (April 2021) - Wei, Yuanrong; Sun, Zuoliang; Song, Xiefa; Sun, Guoxiang; Li, Meng
Graphical abstract: Highlights: E-SFBBR enhanced N removal from carbon limited mariculture wastewater. Current density of 0.1 mA cm −2 performed the best on N removal. N removal pathways related to S and Fe transformations in E-SFBBR were proposed. Abstract: Nitrogen discharged from mariculture industry leads to adjacent aquatic pollution. This study utilized an electrochemically assisted submerged fixed bed bioreactor (E-SFBBR) to treat carbon-limited saline mariculture wastewater and aimed to evaluate the performance and pathways of nitrogen removal by testing the effects of electrical stimulation and different current densities (CD). Electro-stimulation increased nitrogen removal performance of E-SFBBR from 1.1 to 2.2 g N m −2 d −1 to 3.0–3.4 g N m −2 d −1 ; CD of 0.10 mA cm −2 resulted in the highest N removal rate. Results of water quality at different depths and the batch experiment revealed the N removal pathways in E-SFBBR: in the cathode area, nitrogen removal was mainly attributed to the processes of denitrification and dissimilatory nitrate reduction to ammonia; and in the anode area, nitrification and autotrophic denitrification driven by sulfur or iron contributed to nitrogen elimination. These findings provided a promising method for enhancing N removal from carbon-limited mariculture effluents.